The new mode of public governance and public accountability in developing countries: an analtysis with particular reference to Bangladesh - Sarker, Abu Elias (2009)
Public accountability is a fundamental element of good governance. All countries all over the world strive to ensure the accountability of public officials by adopting different kinds of mechanisms. Following the liberal democratic tradition, most countries in the world have relied on the legislative instruments, executive means, judicial and quasi-judicial processes, official rules, codes of conducts, official hierarchies, public hearings, interest groups, media scrutiny and so forth for ensuring public accountability. However, in recent years, the new mode of public governance has brought new dimensions to the discourse on public accountability. This new mode focuses largely on the market- and society-centered mechanisms. This article is an attempt to assess the effectiveness of these market- and society-centered mechanisms in ensuring public accountability in Bangladesh. The article has the following objectives: (a) to explore contemporary debates on the market- and society-centered mechanisms of public accountability; (b) to sketch the state of public accountability in Bangladesh; and (c) to analyze the effectiveness of the market- and society-centered mechanisms in view of the contemporary socio-economic and political dynamics of Bangladesh. - Reproduced.
Keywords: Public administration - Bangladesh; Public administration